An observational study of clinico-pathological characteristics of gynecological tumors and mode of treatment - Ashwini R; Ravi N Patil; Shiny Varghese; Nalini Arun Kumar; Sathyavani C (Asian Journal of Medical Sciences)
Background: Gynecological malignancies are a group of various malignancies of the female reproductive system which included cancers of the ovary, cervix, uterus, vulva, vagina, and also gestational trophoblastic neoplasia.